Cost analysis of tuberculin skin test and the QuantiFERON-TB Gold In-tube test for tuberculosis screening in a correctional setting in Dallas, Texas, USA. Issue 1 (December 2016) - Nijhawan, Ank; Iroh, Princess; Brown, Larry; Winetsky, Daniel; Porsa, Esmaeil
Abstract Background Tuberculosis (TB) disproportionately affects immigrants, HIV-infected individuals, and those living in crowded settings such as homeless shelters and correctional facilities. Although the majority of jails and prisons use a tuberculin skin test (TST) for latent tuberculosis infection (LTBI) screening, limited data exist on the clinical performance and costs of the TST compared to interferon gamma release assays (IGRAs) in this setting. Methods A prospective pilot study comparing cost between TST and an IGRA (QuantiFERON Gold In-tube, QFT-GIT) for the detection of LTBI in a convenience sample of inmates entering the Dallas County Jail (DCJ) was conducted June–October 2014. Participants completed a risk questionnaire, TST placement, QFT-GIT testing, and were offered opt-out HIV-Ab testing. LTBI prevalence based on TST and QFT-GIT results, an evaluation of discordant results and a cost analysis are presented. Results A total of 529 subjects were enrolled. The majority were male (75 %), and 46 % were Black, 29 % White, and 24 % Hispanic. Most (85 %) had been previously incarcerated. Over 28 % of participants were released prior to TST reading, with paired QFT-GIT and TST results available for 351 subjects. Of these, nine (2.6 %) tested positive by TST and 47 (13.4 %) tested positive by QFT-GIT. It costs 23.27 more per inmate per year to screen with QFT-GIT than TST in this population, though the cost per LTBI case detected was nearly three times higher for TST than QFT-GIT (1247 v 460). Conclusions We found a substantially higher rate of QFT-GIT positivity compared to TST in this sample of individuals entering the Dallas County Jail. Although no gold standard exists, this finding may indicate under-recognized LTBI in this setting. QFT-GIT as an initial screening tool was more time-efficient, had four-fold fewer labor costs and provided results on more individuals when compared with the TST. The overall cost of QFT-GIT was 23.27 more per inmate per year, though the cost per LTBI case detected was nearly three times higher for TST than QFT-GIT. Further research is needed to determine the long-term performance of IGRA testing in the correctional setting and the public health implications of pairing QFT-GIT screening with other tests for communicable diseases.